Pengaruh Literasi Ekonomi, Status Ekonomi Orang Tua, Gaya Hidup Dan Religiusitas terhadap Pola Konsumsi Islami di Pondok Pesantren Darul Qur’an Kepulauan Riau - Asmarannida Ari Faatihah (Nomicpedia: Journal of Economics and Business Innovation, 2021)
This study aims to determine the role of human obedience to the application of religious teachings in consumption behavior, namely as a measure of how a person’s perspective on world life tends to affect lifestyle, behavior, and tastes. So when the nature of Israf or excess appears. Allah places limits on His servants in consuming. This study aims to determine the effect of economic literacy, parental economic status, lifestyle, and religiosity on Islamic consumption patterns in Darul Qur’an Islamic Boarding School, Riau Islands. This type of researcher also tested the hypothesis in this study. The results of the study partially show that financial literacy does not affect Islamic consumption patterns, the economic status of parents affects Islamic consumption patterns, lifestyle has no effect on Islamic consumption patterns and religiosity has no effect on Islamic consumption patterns at Darul Qur’an Islamic Boarding School, Riau Islands. Simultaneously the results of the study prove that financial literacy, parent’s economic status, lifestyle, and religiosity simultaneously have a significant effect on Islamic consumption patterns in Darul Qur’an Islamic Boarding School, Riau Islands.